INTEGRATION OF ISLAMIC VALUES IN ENTREPRENEURSHIP CURRICULUM: MODEL ANALYSIS AND ITS IMPACT AT SMKIT KEMILAU BANGSA BATAM - Muhammad Dinariansyah; Dahrul Aman Harahap; Tri Tarwiyani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The development of an entrepreneurship curriculum that integrates Islamic values ​​is a strategic stage to form a generation of entrepreneurs who are not only professionally competent but also have noble morals and in the increasingly complex era of globalization, entrepreneurial skills are a crucial aspect that must be possessed by vocational high school graduates. However, the main challenge in implementing an entrepreneurship program based on Islamic values ​​lies in the degree of ensuring a balance between learning business skills and internalizing Islamic character. This study is targeted to analyze the model of integration of Islamic values ​​in the entrepreneurship curriculum at SMKIT Kemilau Bangsa Batam and evaluate its impact on student competence and character. The research method currently implemented is based on a qualitative descriptive perspective, comprehensively exploring the degree of the concept of integration of Islamic values ​​implemented in the planning, organization, implementation, and evaluation of entrepreneurship programs. Regardless of these conditions, this study is targeted to identify factors that influence the effectiveness of the program. It is hoped that this study will provide a perspective on the optimal strategy as an effort to linearize entrepreneurship learning supported by Islamic values, as well as provide policy recommendations to improve the effectiveness of the curriculum based on Islamic values. The output of this study is a model of an entrepreneurship curriculum based on Islamic values ​​that can be a reference for other schools in developing innovative and sustainable Islamic entrepreneurship programs.